Cable Whip In Shuttle Car Trailing Cables - G. J. Conroy (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Cable whip occurring during normal movement of a shuttle car can result in a personnel hazard and excessive tensions in the cable. This Bureau of Mines report discusses preferred payout and reel-in torque settings to reduce cable whip. A simplified adjustment procedure is described.